Seismic performance assessment of plain concrete arch bridges under near-field earthquakes using incremental dynamic analysis. (December 2019) - Yazdani, M.; Jahdngiri, V.; Marefat, M.S.
Abstract: In the railway network of Iran, a large number of masonry arch bridges exist which most of them was constructed 80 years ago. Despite these types of bridges have shown an appropriate behavior under the influence of gravity (vertical) loads, they have not been designed seismically. Concerning to the seismic hazard zoning map of Iran, most of these railway infrastructures are placed in the very high seismicity zones and constructed near the major faults. So the seismic assessment of these types of bridges has become a significant subject for the engineers to explain the failure and seismic performance levels of these structures. Thus, they can be rehabilitated or removed if it is found required. Among various methods for seismic estimation of the capacity of the structures under seismic loading, the non-linear dynamic method or the incremental dynamic analysis (IDA) may be mentioned as the most precise and complete method for near-field excitations. For this purpose, by selecting 28 near-field earthquake records, this study has seismically surveyed two railway masonry arch bridges, which are respectively placed in the kilometers 23 (2L20 bridge) and 24 (5L06 bridge) of the old railway of Tehran-Qom. The macro-modeling approach was used in the finite element method. In total, 316 non-linear dynamic analyses have been carried out for the seismic assessment of the masonry arch bridges under near-field ground motion. The results found from the IDA analysis specified that the near-field seismic performance of the masonry arch bridge with lower span length (i.e., 5L06 bridge) is safer than the bridge with longer span length (i.e., 2L20 bridge). Mostly, it has to decide to retrofit the masonry bridge with longer span length to improve their performance since the seismic behavior of those has been found inappropriate under near-field earthquakes. Highlights: FE simulation has performed to evaluated seismic response of masonry arch bridges 316 incremental dynamic analysis (IDA) for near-field earthquakes has been conducted The statistical analysis of the obtained results indicated that the arch bridges perfectly obey the Gamma distribution IDA showed that the seismic behavior of these structures completely depends on their geometrical and mechanical features The results show that the response of these infrastructures under near-field earthquakes is sensitive to velocity response